Scientific-Methodological Approaches to Forming Integrated Content of the Subject «Person and Society» in 1990-s - Areshonkov, Volodymyr (Pedagogical Discourse, 2014)
The process of forming integrated content of the subject «Person and Society» in 1990-s on the basis of education humanization has been studied in the article. The conclusion is made that the declared civilized approach, put into the bases of the course, hasn’t been widespread realized in practice during 1990-s, because such content of teaching was demanded from the teacher, which couldn’t be realized by the teacher himself or herself. Integration of the content took place taking into account the combination of knowledge on anthropology, medicine, psychology, philosophy, social-political disciplines, law and economic sciences.